Railway strike, 1911 (1911)
1911 1880-1914 "Railway strike, 1911" [T0055.jpg], 1911 There was industrial unrest among railway workers due to high prices, long hours and dissatisfaction with the slow moving conciliation system. An unofficial strike started in Liverpool and spread to other cities, prompting sympathetic action from dockers, carters and other transport workers. The four rail unions made the strike official on 18 August 1911, by which time an estimated 70,000 workers (including 20,000 railway workers) were on strike and troops were mobilised. After Government mediation, the unions' grievances were brought forward to a Royal Commission called to discuss industrial relations in the railways. In 1913, three of the rail unions combined to form the National Union of Railwaymen.